2007
DOI: 10.1007/s00425-006-0476-9
|View full text |Cite
|
Sign up to set email alerts
|

Iron assimilation and transcription factor controlled synthesis of riboflavin in plants

Abstract: Iron homeostasis is vital for many cellular processes and requires a precise regulation. Several iron efficient plants respond to iron starvation with the excretion of riboflavin and other flavins. Basic helix-loop-helix transcription factors (TF) are involved in the regulation of many developmental processes, including iron assimilation. Here we describe the isolation and characterisation of two Arabidopsis bHLH TF genes, which are strongly induced under iron starvation. Their heterologous ectopic expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 54 publications
3
69
0
Order By: Relevance
“…Specifically, Helicobacter pylori does not produce siderophores under Fe-limited conditions, but produces riboflavin that can reduce Fe(III) in ferritins (12). Sugar beet and sunflower roots excrete micromolar amounts of riboflavin-5Ј and riboflavin-3Ј sulfate when grown in Fe-poor soils, leading to reduction and uptake of Fe (42). In Pichia gulliermondii, growth in low-Fe(III) medium leads to riboflavin excretion, whereas mutations preventing ribof lavin overproduction significantly slow Fe-limited growth (43).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Helicobacter pylori does not produce siderophores under Fe-limited conditions, but produces riboflavin that can reduce Fe(III) in ferritins (12). Sugar beet and sunflower roots excrete micromolar amounts of riboflavin-5Ј and riboflavin-3Ј sulfate when grown in Fe-poor soils, leading to reduction and uptake of Fe (42). In Pichia gulliermondii, growth in low-Fe(III) medium leads to riboflavin excretion, whereas mutations preventing ribof lavin overproduction significantly slow Fe-limited growth (43).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, however, free flavins, especially riboflavin, have been detected in the roots and/or root exudates of some taxonomically unrelated dicotyledonous plants, including tobacco and sunflower, growing under conditions of Fe deficiency [3,4]. Recently, Vorwieger et al [5] confirmed that the ectopic expression of Arabidopsis basic helix-loop-helix transcription factors, which are induced under Fe deficiency, induced riboflavin excretion in transgenic hairy roots of tobacco and sunflower, although not in those of tomato, which do not excrete riboflavin under Fe-deficient conditions. Hence, riboflavin secretion under Fe deficiency is genetically regulated.…”
Section: Introductionmentioning
confidence: 99%
“…The identiWcation of transcription factors in Arabidopsis is eased by the availability of the complete genome sequence and functional genome projects. In a recent study Vorwieger et al (2007) identiWed two iron-regulated BHLH genes whose function in Arabidopsis was however, not investigated any further by these authors. Here, we studied regulation of these two BHLH genes (BHLH038, BHLH039) and of their closest homologs (BHLH100, BHLH101) that we termed subgroup Ib BHLH genes in leaves and roots in various nutritional situations as well as in mutant backgrounds and split-root situations related to iron deWciency.…”
Section: Introductionmentioning
confidence: 99%